INFLUENCE OF COMPANY VALUE INFORMATION, DIVIDEND POLICY, AND CAPITAL STRUCTURE ON STOCK PRICE - Rita Syofyan; Defriko Gusma Putra; Riyadi Aprayuda (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2020)
This study aims to examine: 1) The effect of company value information in this case the price book value (PBV) on stock prices, 2) The effect of dividend policy in this case the dividend payout ratio (DPR) on stock prices, 3) The effect of capital structure in terms of This is a debt to equity ratio (DER) to stock prices. This type of research is classified as research that is causative. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2008 to 2010. The sample selection is by purposive sampling method. The data used in this study include secondary data. Data collection techniques with documentation techniques. The analysis used is multiple linear regression. The results showed that: 1) Company value had no effect on stock prices, where the significance value was 0.031 <0.05 and the value of t count> t table was 2.214> 1.995 but the negative β value was -0.028 (H1 was rejected). 2) Dividend policy has a significant positive effect on stock prices, where the significance value is 0.034 <0.05 and the value of t arithmetic> t table is 2.171> 1.995 and a positive β value of 0.032 (H2 is accepted). 3) Capital structure has a significant negative effect on stock prices, where the significance value is 0.006 <0.05 and the value of t arithmetic> t table is 2.861> 1.995 and the negative β value is -0.040 (H3 accepted).